Pembentukan Karakter Santri Melalui Sistem Single Sex Education - Abdul Malik; Syafri Martabe Rizka Nasution (Prodi Pendidikan Keagamaan Islam, 2024)
This study aims to determine how the character formation of students through the implementation of the Single Sex Education system at the Darul Ikhlas Islamic Boarding School in Dalan Lidang, and to identify supporting and inhibiting factors in its implementation. This study uses a qualitative approach with field research. Data collection techniques were carried out through observation, interviews, and documentation. The results show that the character formation of students at the Darul Ikhlas Islamic Boarding School is carried out through Islamic boarding school culture, compliance with applicable regulations, and through various group activities that instill the values of discipline and responsibility. The methods used in the process of internalizing character values include exemplary behavior, advice, demonstrations, and discussions. Supporting factors for the implementation of the Single Sex Education system include adequate facilities and infrastructure, effective storytelling media, and a dormitory system that supports intensive character development. Meanwhile, inhibiting factors include busy parents, the influence of the environment outside the Islamic boarding school, and the negative influence of mass media. Thus, the implementation of the Single Sex Education system at the Darul Ikhlas Islamic Boarding School in Dalan Lidang has significantly contributed to shaping the character of students who are disciplined, responsible, and virtuous, despite still facing several external obstacles.